Spontaneous plant recolonization on reclaimed post-coal mining sites in East Kalimantan, Indonesia: Native versus alien and succession progress - LIA HAPSARI; Trimanto Trimanto; Sugeng Budiharta (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hapsari L, Trimanto, Budiharta S. 2020. Spontaneous plant recolonization on reclaimed post-coal mining sites in East Kalimantan, Indonesia: Native versus alien and succession progress. Biodiversitas 21: 2003-2017. Comparative vegetation analyses subjected to recolonization of spontaneous plants were carried out in two post-coal mining reclamation sites, with different ages of reclamation, specifically 9 years old and 17 years old, in Bontang, East Kalimantan. This study aims to determine the spontaneous plant diversity and composition, identify the spontaneous alien plant species invasion (IAS), analyze the underlying micro-climates and soil factors and their association to the spontaneous plant recolonization, also to evaluate the succession progress. Results showed that both reclamation sites have undergone some vegetation and environmental improvements. The plant succession stage of both sites was identified at the same stage, as establishment phase of early-succession stage in transition to mid-succession stage. The spontaneous plants were comprised of two layers, i.e. (i) understories include grasses, ferns, lianas, herbs, shrubs and tree seedlings; and (ii) saplings include some of trees and small trees. Plant diversity indices on both sites were in moderate category. At understory layer, the 9-y.o. site was mostly dominated by grass Polytrias indica, whereas the 17-y.o. site was dominated by shrub Asystasia gangetica. At sapling layer, the 9-y.o. site was mostly dominated by Glochidion obscurum, whereas the 17-y.o. site was dominated by Macaranga tanarius. Dominant pioneer tree and shrub species in two reclamation sites mostly from general species component of secondary tropical forests from the families Euphorbiaceae, Phyllantaceae, Melastomaceae, Leguminosae, and Lamiaceae. It was recorded seven IAS in the 9-y.o. site, which six out of seven species were dominant. Meanwhile, in the 17-y.o. site was recorded eight IAS but only four species were dominant. Two dominant noxious weed species were also identified. Each IAS and noxious weed species has invasiveness traits that make them well-grown, successfully recolonized and invaded the reclamation site. Environmental factors include air temperature, air moisture, and light intensity; and soil conditions include pH, C/N ratio and physicochemical properties affected the variation of spontaneous plant establishment on each reclamation site. These comparative study findings may become inputs for coal mining operations management to evaluate and improve their reclamation program; such as by soil reconditions, controlling the populations of IAS, and planting more intensively of native tree species.